Flame-retardant fiber fireproof thermal-insulation knitted composite cotton and preparation process thereof

By using a composite structure of a knitted cotton matrix layer, fiber layer and resin layer in the knitted composite material, and adding functional additives such as modified glass fiber, the problem of difficult to coordinate and improve the thermal insulation and flame retardant fire resistance in the prior art is solved, and efficient thermal insulation, flame retardant and fire resistance and corrosion resistance are achieved.

CN119840263AActive Publication Date: 2025-04-18JINJIANG ZIRAN CHEM FIBER MFG

Patent Information

Application Number
CN202510322357.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

When existing knitted composite materials improve thermal insulation performance, their flame retardant and fire-retardant properties are easily degraded, and their corrosion resistance and water immersion stability are poor, which limits the efficiency of the product.

Method used

The composite structure of the knitted cotton matrix layer, the upper and lower fiber layers and the upper and lower resin layers is adopted. The fiber layer is braided by polyester fiber and spandex fiber, and the resin layer is molded and cured by resin composite agent. Modified glass fibers, glass microbeads, magnesium hydroxide flame retardant and a reinforcing agent are added to enhance performance.

Benefits of technology

The coordinated improvement of thermal insulation and flame retardant fire resistance is achieved, while improving the product's corrosion resistance and water immersion stability, significantly improving the use efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119840263A_ABST
    Figure CN119840263A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite layer structures, in particular to flame-retardant fiber fireproof heat-preservation knitted composite cotton and a preparation process thereof.The knitted composite cotton comprises a knitted cotton base body layer, fiber layers are fixedly arranged on the upper surface and the lower surface of the knitted cotton base body layer, and the two fiber layers are formed by weaving polyester fibers and spandex fibers; resin layers are fixedly arranged on the outer surfaces of the two fiber layers, and are formed by mould pressing and curing of a resin complexing agent. The knitted composite cotton is formed by compounding a knitted cotton matrix layer, an upper fiber layer, a lower fiber layer, an upper resin layer and a lower resin layer, and a resin body in a resin complexing agent is prepared from bisphenol A epoxy resin, a dicyandiamide curing agent, 1-benzyl-2-methylimidazole and a silane coupling agent KH560 to form matrix liquid. The added glass beads and the magnesium hydroxide flame retardant are used as functional aids, and the modified glass fibers and the reinforcing agent are coordinated and synergic, so that the obtained knitted composite cotton has excellent heat preservation, flame retardance and fire resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite cotton structures, and in particular to a flame-retardant fiber fireproof and heat-insulating knitted composite cotton and a preparation process thereof. Background Art

[0002] Fabrics play a great role in human life. In addition to using fiber fabrics directly, they can also be combined with resin matrices to form composite materials. Fiber-reinforced composite materials have been widely used in the engineering field due to their high strength and high modulus.

[0003] In order to improve the thermal insulation performance of the product, the existing knitted composite materials easily lead to a decrease in the flame retardant and fireproof performance of the product. The thermal insulation and flame retardant properties of the product are difficult to improve in a coordinated manner. At the same time, the corrosion resistance and water immersion stability of the product are poor, which limits the use efficiency of the product. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a flame retardant fiber fireproof heat-insulating knitted composite cotton and a preparation process thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a flame-retardant fiber fireproof heat-insulating knitted composite cotton, the knitted composite cotton comprising a knitted cotton base layer, the upper surface and the lower surface of the knitted cotton base layer are fixed with fiber layers, and the two fiber layers are woven by polyester fiber and spandex fiber in a weight ratio of 1:1; The outer surfaces of the two fiber layers away from the knitted cotton matrix layer are fixed with resin layers, and the resin layers are formed by molding and curing of the resin composite agent. The molding and curing temperature is 130-135° C., the molding pressure is 10 MPa, and the molding time is 12 hours.

[0006] Preferably, the preparation method of the knitted cotton base layer is: 35-40 parts by weight of 100S / 2 cotton yarn and 30-35 parts by weight of 30D spandex yarn are knitted into cotton fabric, and then the cotton fabric is immersed in a sufficient amount of 5% by weight sodium hydroxide solution for alkali washing. After the treatment, the fabric is washed with water and dried to obtain a knitted cotton base layer.

[0007] Preferably, the resin composite comprises the following raw materials in parts by weight: 10-15 parts of modified glass fiber, 5-8 parts of glass microspheres, 4-7 parts of magnesium hydroxide flame retardant, 6-10 parts of strengthening agent, and 45-55 parts of resin.

[0008] Preferably, the resin body is prepared by using bisphenol A epoxy resin, dicyandiamide curing agent, 1-benzyl-2-methylimidazole, and silane coupling agent KH560 in a weight ratio of 50:10:3:2.

[0009] Preferably, the preparation method of the modified glass fiber is: S01: placing the glass fiber in a sufficient amount of a hydrogen peroxide solution with a mass fraction of 5-8%, stirring and mixing well, then washing and drying to obtain dry glass fiber; placing the dry glass fiber in a proton irradiation box for irradiation for 20-30 minutes, with an irradiation power of 350-400W, and completing the irradiation to obtain irradiated glass fiber; S02: adding 4-6 parts of kaolin powder and 1-3 parts of sodium silicate solution to 5-8 parts of phosphate buffer solution by weight, and then adding 2-4 parts of boron nitride, stirring evenly, to obtain a first addition solution; Add 3-5 parts of silicon carbide whiskers and 2-4 parts of sodium carboxymethyl cellulose to 5-8 parts of chitosan solution by weight, and stir evenly to obtain a second additive solution; S03: The first additive liquid and the second additive liquid were mixed in a weight ratio of 5:3, and ball-milled at a speed of 1500 r / min for 2 h to obtain a modified liquid; S04: adding the irradiated glass fiber to a modification liquid of 4-7 times the total weight of the irradiated glass fiber, stirring and modifying the fiber, and after the stirring is completed, filtering and drying to obtain the modified glass fiber.

[0010] Preferably, the mass fraction of the sodium silicate solution is 4-6%; the pH value of the phosphate buffer solution is 5.5; and the mass fraction of the chitosan solution is 3-5%.

[0011] Preferably, the stirring speed of the stirring modification treatment is 550-650 r / min, and the stirring is for 30 min.

[0012] Preferably, the preparation method of the tonic agent is: S11: preheating the flaky talc at 55-60° C. for 1 h, then immersing the preheated flaky talc in a lanthanum chloride solution 3-5 times the total weight of the preheated flaky talc, stirring at a stirring speed of 500-700 r / min, stirring for 2 h, and after the stirring is completed, filtering and drying to obtain a flaky talc agent doped with lanthanum; S12: The lanthanum-doped flaky talc and the strength-regulating and tonic liquid are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain the strength-regulating and tonic agent.

[0013] Preferably, the mass fraction of the lanthanum chloride solution is 3-6%.

[0014] Preferably, the strength-regulating and tonic liquid comprises the following raw materials in parts by weight: 3-4 parts of nano-alumina, 4-6 parts of sodium lignin sulfonate solution, 2-3 parts of hydroxyapatite, 1-2 parts of yttrium oxide and 1-2 parts of sodium alginate solution.

[0015] Preferably, the mass fraction of the sodium lignin sulfonate solution is 5-8%; the mass fraction of the sodium alginate solution is 3-6%.

[0016] The present invention also provides a preparation process of flame retardant fiber fireproof heat-insulating knitted composite cotton, comprising the following steps: Step 1, preparing a knitted cotton base layer; Step 2: preparing a fiber layer, and arranging the fiber layer on the upper surface and the lower surface of the knitted cotton base layer; Step three: prepare a resin composite, and arrange a resin layer on the outer surface of the fiber layer away from the knitted cotton matrix layer to obtain flame-retardant fiber fireproof and heat-insulating knitted composite cotton.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The knitted composite cotton of the present invention is composited by a knitted cotton base layer, two upper and lower fiber layers and two upper and lower resin layers. The knitted cotton base layer is knitted by cotton yarn and spandex yarn. The resin body in the resin composite is prepared by bisphenol A epoxy resin, dicyandiamide curing agent, 1-benzyl-2-methylimidazole and silane coupling agent KH560 to form a base liquid. Glass microbeads and magnesium hydroxide flame retardant are added as functional additives. At the same time, the modified glass fiber and the strengthening agent are coordinated and matched to enhance the effect together. The obtained knitted composite cotton has excellent heat preservation, flame retardancy and fireproof properties, and the two are coordinated and improved. At the same time, the corrosion resistance and water immersion stability of the product are remarkable. The modified glass fiber adopts glass fiber to be improved by oxidation activation with hydrogen peroxide solution, and then by proton irradiation, coordinated optimization and improvement, and at the same time, the modified liquid is stirred and improved to coordinately improve the glass fiber, optimize the product performance effect, and the first additive liquid and the second additive liquid in the modified liquid are mutually ball-milled and adjusted. The first additive liquid adopts kaolin. The invention discloses a novel method for preparing a novel glass fiber reinforced composite material, and the method comprises the steps of: adjusting and adjusting the performance of the composite material by mixing the sodium silicate solution, boron nitride and other raw materials in the lamellar kaolin system, optimizing the system performance stability, and at the same time, the second additive liquid is obtained by uniformly stirring silicon carbide whiskers, sodium carboxymethyl cellulose and chitosan solution, and further enhancing the interface of the raw materials of the system through the whisker-like silicon carbide whisker system, thereby improving the glass fiber through the modified liquid obtained by the mutual coordination of the first additive liquid and the second additive liquid, and further improving the performance of the product; the reinforcing agent adopts flaky talcum powder as the matrix, and the reinforcing agent is further ball-milled and improved by the reinforcing agent, and the nano-alumina in the reinforcing agent is coordinated with hydroxyapatite to coordinate with the flaky talcum powder, and the sodium lignin sulfonate solution, yttrium oxide and sodium alginate solution are added to blend and adjust, and the reinforcing agent obtained by the mutual coordination and adjustment between the raw materials is enhanced with the reinforcing effect of the modified glass fiber, and the performance of the product is further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a layered structure diagram of the present invention. DETAILED DESCRIPTION

[0019] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] like Figure 1As shown, a flame retardant fiber fireproof heat-insulating knitted composite cotton of this embodiment, the knitted composite cotton comprises a knitted cotton base layer 1, and a fiber layer 2 is fixedly provided (for example, by hot pressing, stitching, etc.) on the upper surface and the lower surface of the knitted cotton base layer 1, and the two fiber layers 2 are woven by polyester fiber and spandex fiber in a weight ratio of 1:1; The outer surfaces of the two fiber layers 2 away from the knitted cotton base layer 1 are fixed with a resin layer 3, which is formed by molding and curing the resin composite, with a molding curing temperature of 130-135°C, a molding pressure of 10Mpa, and a molding time of 12h.

[0021] The preparation method of the knitted cotton substrate layer of this embodiment is: 35-40 parts by weight of 100S / 2 cotton yarn and 30-35 parts by weight of 30D spandex yarn are knitted into cotton fabric, and then the cotton fabric is immersed in a sufficient amount of 5% by weight sodium hydroxide solution for alkali washing. After the treatment, the fabric is washed with water and dried to obtain a knitted cotton base layer.

[0022] The resin composite of this embodiment includes the following raw materials in parts by weight: 10-15 parts of modified glass fiber, 5-8 parts of glass beads, 4-7 parts of magnesium hydroxide flame retardant, 6-10 parts of conditioning and strengthening agent, 45-55 parts of resin body; the resin body is prepared by bisphenol A type epoxy resin, dicyandiamide curing agent, 1-benzyl-2-methylimidazole, and silane coupling agent KH560 according to the weight ratio of 50:10:3:2.

[0023] The preparation method of the modified glass fiber of this embodiment is: S01: placing the glass fiber in a sufficient amount of a hydrogen peroxide solution with a mass fraction of 5-8%, stirring and mixing well, then washing and drying to obtain dry glass fiber; placing the dry glass fiber in a proton irradiation box for irradiation for 20-30 minutes, with an irradiation power of 350-400W, and completing the irradiation to obtain irradiated glass fiber; S02: adding 4-6 parts of kaolin powder and 1-3 parts of sodium silicate solution to 5-8 parts of phosphate buffer solution by weight, and then adding 2-4 parts of boron nitride, stirring evenly, to obtain a first addition solution; Add 3-5 parts of silicon carbide whiskers and 2-4 parts of sodium carboxymethyl cellulose to 5-8 parts of chitosan solution by weight, and stir evenly to obtain a second additive solution; S03: The first additive liquid and the second additive liquid were mixed in a weight ratio of 5:3, and ball-milled at a speed of 1500 r / min for 2 h to obtain a modified liquid; S04: adding the irradiated glass fiber to a modification liquid of 4-7 times the total weight of the irradiated glass fiber, stirring and modifying the fiber, and after the stirring is completed, filtering and drying to obtain the modified glass fiber.

[0024] The mass fraction of the sodium silicate solution in this embodiment is 4-6%; the pH value of the phosphate buffer solution is 5.5; and the mass fraction of the chitosan solution is 3-5%.

[0025] The stirring speed of the stirring modification treatment in this embodiment is 550-650r / min, and the stirring is 30min.

[0026] The preparation method of the tonic stimulant of this embodiment is as follows: S11: preheating the flaky talc at 55-60° C. for 1 h, then immersing the preheated flaky talc in a lanthanum chloride solution 3-5 times the total weight of the preheated flaky talc, stirring at a stirring speed of 500-700 r / min, stirring for 2 h, and after the stirring is completed, filtering and drying to obtain a flaky talc agent doped with lanthanum; S12: The lanthanum-doped flaky talc and the strength-regulating and tonic liquid are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain the strength-regulating and tonic agent.

[0027] The mass fraction of the lanthanum chloride solution of the present embodiment is 3-6%.

[0028] The strength-regulating and tonic liquid of this embodiment comprises the following raw materials in parts by weight: 3-4 parts of nano-alumina, 4-6 parts of sodium lignin sulfonate solution, 2-3 parts of hydroxyapatite, 1-2 parts of yttrium oxide and 1-2 parts of sodium alginate solution.

[0029] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5-8%; the mass fraction of the sodium alginate solution is 3-6%.

[0030] The preparation process of a flame retardant fiber fireproof heat-insulating knitted composite cotton of this embodiment includes the following steps: Step 1, preparing a knitted cotton base layer 1; Step 2: preparing the fiber layer 2, and arranging the fiber layer 2 on the upper surface and the lower surface of the knitted cotton base layer 1; Step three: prepare a resin composite, and arrange a resin layer 3 on the outer surface of the fiber layer 2 away from the knitted cotton base layer 1, so as to obtain a flame retardant fiber fireproof and heat-insulating knitted composite cotton.

[0031] Example 1: Figure 1 As shown, a flame retardant fiber fireproof heat-insulating knitted composite cotton, the knitted composite cotton comprises a knitted cotton base layer 1, the upper surface and the lower surface of the knitted cotton base layer 1 are fixed with fiber layers 2, and the two fiber layers 2 are woven by polyester fiber and spandex fiber in a weight ratio of 1:1; The outer surfaces of the two fiber layers 2 away from the knitted cotton base layer 1 are fixed with a resin layer 3, and the resin layer 3 is formed by molding and curing the resin composite, with a molding curing temperature of 130°C, a molding pressure of 10 MPa, and a molding time of 12 hours.

[0032] The preparation method of the knitted cotton substrate layer of this embodiment is: 35 parts of 100S / 2 cotton yarn and 30 parts of 30D spandex yarn are knitted into cotton fabric by weight, and then the cotton fabric is immersed in a sufficient amount of 5% by mass sodium hydroxide solution for alkaline washing. After the treatment, it is washed with water and dried to obtain a knitted cotton base layer.

[0033] The resin composite of this embodiment includes the following raw materials in parts by weight: 10 parts of modified glass fiber, 5 parts of glass beads, 4 parts of magnesium hydroxide flame retardant, 6 parts of conditioning and strengthening agent, and 45 parts of resin body; the resin body is prepared with bisphenol A type epoxy resin, dicyandiamide curing agent, 1-benzyl-2-methylimidazole, and silane coupling agent KH560 according to the weight ratio of 50:10:3:2.

[0034] The preparation method of the modified glass fiber of this embodiment is: S01: placing the glass fiber in a sufficient amount of a 5% by mass hydrogen peroxide solution and stirring and mixing the solution thoroughly, then washing and drying the solution to obtain a dry glass fiber; placing the dry glass fiber in a proton irradiation box and irradiating the solution for 20 minutes at an irradiation power of 350W, and then completing the irradiation to obtain an irradiated glass fiber; S02: Add 4 parts of kaolin powder and 1 part of sodium silicate solution to 5 parts of phosphate buffer solution by weight, then add 2 parts of boron nitride, stir evenly, and obtain a first addition solution; Add 3 parts of silicon carbide whiskers and 2 parts of sodium carboxymethyl cellulose to 5 parts of chitosan solution by weight, stir evenly, and obtain a second additive solution; S03: The first additive liquid and the second additive liquid were mixed in a weight ratio of 5:3, and ball-milled at a speed of 1500 r / min for 2 h to obtain a modified liquid; S04: adding the irradiated glass fiber into a modification liquid of 4 times the total weight of the irradiated glass fiber, stirring and modifying the fiber, and after the stirring is completed, filtering and drying to obtain the modified glass fiber.

[0035] The mass fraction of the sodium silicate solution in this embodiment is 4%; the pH value of the phosphate buffer solution is 5.5; and the mass fraction of the chitosan solution is 3%.

[0036] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring is 30 min.

[0037] The preparation method of the tonic stimulant of this embodiment is as follows: S11: preheating the flaky talc at 55° C. for 1 h, then immersing the preheated flaky talc in a lanthanum chloride solution 3 times the total weight of the preheated flaky talc, stirring at a stirring speed of 500 r / min for 2 h, and after the stirring is completed, filtering and drying to obtain a flaky talc agent doped with lanthanum; S12: The lanthanum-doped flaky talc and the strength-regulating and tonic liquid are mixed in a weight ratio of 5:3, and ball-milled at a ball-milling speed of 1000 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the strength-regulating and tonic agent.

[0038] The mass fraction of the lanthanum chloride solution of the present embodiment is 3%.

[0039] The strength-regulating and tonic liquid of this embodiment comprises the following raw materials in parts by weight: 3 parts of nano-alumina, 4 parts of sodium lignin sulfonate solution, 2 parts of hydroxyapatite, 1 part of yttrium oxide and 1 part of sodium alginate solution.

[0040] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%; the mass fraction of the sodium alginate solution is 3%.

[0041] The preparation process of a flame retardant fiber fireproof heat-insulating knitted composite cotton of this embodiment includes the following steps: Step 1, preparing a knitted cotton base layer 1; Step 2: preparing a fiber layer 2, and arranging the fiber layer 2 on the upper surface and the lower surface of the knitted cotton base layer 1; Step 3, prepare the resin composite: the modified glass fiber, glass beads, magnesium hydroxide flame retardant, tonic agent and resin are mixed evenly to obtain the resin composite; the resin layer 3 is formed by molding and curing the resin composite on the outer surface of the fiber layer 2 away from the knitted cotton base layer 1, and the flame retardant fiber fireproof and heat-insulating knitted composite cotton is obtained.

[0042] Example 2: Figure 1 As shown, a flame retardant fiber fireproof heat-insulating knitted composite cotton, the knitted composite cotton comprises a knitted cotton base layer 1, the upper surface and the lower surface of the knitted cotton base layer 1 are fixed with fiber layers 2, and the two fiber layers 2 are woven by polyester fiber and spandex fiber in a weight ratio of 1:1; The outer surfaces of the two fiber layers 2 away from the knitted cotton base layer 1 are fixed with a resin layer 3, and the resin layer 3 is formed by molding and curing the resin composite, with a molding curing temperature of 135°C, a molding pressure of 10 MPa, and a molding time of 12 hours.

[0043] The preparation method of the knitted cotton substrate layer of this embodiment is: 40 parts of 100S / 2 cotton yarn and 35 parts of 30D spandex yarn are knitted into cotton fabric by weight, and then the cotton fabric is immersed in a sufficient amount of sodium hydroxide solution with a mass fraction of 5% for alkali washing. After the treatment, the fabric is washed with water and dried to obtain a knitted cotton base layer.

[0044] The resin composite of this embodiment includes the following raw materials in parts by weight: 15 parts of modified glass fiber, 8 parts of glass beads, 7 parts of magnesium hydroxide flame retardant, 10 parts of conditioning and strengthening agent, and 55 parts of resin body; the resin body is prepared with bisphenol A type epoxy resin, dicyandiamide curing agent, 1-benzyl-2-methylimidazole, and silane coupling agent KH560 according to the weight ratio of 50:10:3:2.

[0045] The preparation method of the modified glass fiber of this embodiment is: S01: placing the glass fiber in a sufficient amount of 8% by mass hydrogen peroxide solution and stirring and mixing it thoroughly, then washing and drying it to obtain dry glass fiber; placing the dry glass fiber in a proton irradiation box and irradiating it for 30 minutes at an irradiation power of 400W, and then completing the irradiation to obtain irradiated glass fiber; S02: adding 6 parts of kaolin powder and 3 parts of sodium silicate solution to 8 parts of phosphate buffer solution by weight, and then adding 4 parts of boron nitride, stirring evenly, to obtain a first addition solution; Add 5 parts of silicon carbide whiskers and 4 parts of sodium carboxymethyl cellulose to 8 parts of chitosan solution by weight, stir evenly, and obtain a second additive solution; S03: The first additive liquid and the second additive liquid were mixed in a weight ratio of 5:3, and ball-milled at a speed of 1500 r / min for 2 h to obtain a modified liquid; S04: adding the irradiated glass fiber to a modification liquid of 7 times the total weight of the irradiated glass fiber, stirring and modifying the fiber, and after the stirring is completed, filtering and drying to obtain the modified glass fiber.

[0046] The mass fraction of the sodium silicate solution in this embodiment is 6%; the pH value of the phosphate buffer solution is 5.5; and the mass fraction of the chitosan solution is 5%.

[0047] The stirring speed of the stirring modification treatment in this embodiment is 650 r / min, and the stirring is 30 min.

[0048] The preparation method of the tonic stimulant of this embodiment is as follows: S11: preheating the flaky talc at 60° C. for 1 h, then immersing the preheated flaky talc in a lanthanum chloride solution with a weight that is 5 times the total weight of the preheated flaky talc, stirring at a stirring speed of 700 r / min for 2 h, and after the stirring is completed, filtering and drying to obtain a flaky talc agent doped with lanthanum; S12: The lanthanum-doped flaky talc and the strength-regulating and tonic liquid are mixed in a weight ratio of 5:3, and ball-milled at a ball-milling speed of 1500 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the strength-regulating and tonic agent.

[0049] The mass fraction of the lanthanum chloride solution of the present embodiment is 6%.

[0050] The strength-regulating and tonic liquid of this embodiment comprises the following raw materials in parts by weight: 4 parts of nano-alumina, 6 parts of sodium lignin sulfonate solution, 3 parts of hydroxyapatite, 2 parts of yttrium oxide and 2 parts of sodium alginate solution.

[0051] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 8%; the mass fraction of the sodium alginate solution is 6%.

[0052] The preparation process of a flame retardant fiber fireproof heat-insulating knitted composite cotton of this embodiment includes the following steps: Step 1, preparing a knitted cotton base layer 1; Step 2: preparing the fiber layer 2, and arranging the fiber layer 2 on the upper surface and the lower surface of the knitted cotton base layer 1; Step 3, prepare the resin composite: the modified glass fiber, glass beads, magnesium hydroxide flame retardant, tonic agent and resin are mixed evenly to obtain the resin composite; the resin layer 3 is formed by molding and curing the resin composite on the outer surface of the fiber layer 2 away from the knitted cotton base layer 1, and the flame retardant fiber fireproof and heat-insulating knitted composite cotton is obtained.

[0053] Example 3: Figure 1 As shown, a flame retardant fiber fireproof heat-insulating knitted composite cotton, the knitted composite cotton comprises a knitted cotton base layer 1, the upper surface and the lower surface of the knitted cotton base layer 1 are fixed with fiber layers 2, and the two fiber layers 2 are woven by polyester fiber and spandex fiber in a weight ratio of 1:1; The outer surfaces of the two fiber layers 2 away from the knitted cotton base layer 1 are fixed with a resin layer 3, and the resin layer 3 is formed by molding and curing the resin composite, with a molding curing temperature of 132°C, a molding pressure of 10 MPa, and a molding time of 12 hours.

[0054] The preparation method of the knitted cotton substrate layer of this embodiment is: 37.5 parts of 100S / 2 cotton yarn and 32.5 parts of 30D spandex yarn are knitted into cotton fabric by weight, and then the cotton fabric is immersed in a sufficient amount of 5% by mass sodium hydroxide solution for alkaline washing. After the treatment, it is washed with water and dried to obtain a knitted cotton base layer.

[0055] The resin composite of this embodiment includes the following raw materials in parts by weight: 12.5 parts of modified glass fiber, 6.5 parts of glass beads, 5.5 parts of magnesium hydroxide flame retardant, 8 parts of conditioning and strengthening agent, and 50 parts of resin body; the resin body is prepared with bisphenol A type epoxy resin, dicyandiamide curing agent, 1-benzyl-2-methylimidazole, and silane coupling agent KH560 according to the weight ratio of 50:10:3:2.

[0056] The preparation method of the modified glass fiber of this embodiment is: S01: placing the glass fiber in a sufficient amount of a hydrogen peroxide solution with a mass fraction of 6.5% and stirring and mixing the solution thoroughly, then washing and drying the solution to obtain a dry glass fiber; placing the dry glass fiber in a proton irradiation box and irradiating the solution for 25 minutes at an irradiation power of 375 W, and then completing the irradiation to obtain an irradiated glass fiber; S02: Add 5 parts of kaolin powder and 2 parts of sodium silicate solution to 6.5 parts of phosphate buffer solution by weight, then add 3 parts of boron nitride, stir evenly, and obtain a first addition solution; Add 4 parts of silicon carbide whiskers and 3 parts of sodium carboxymethyl cellulose to 6.5 parts of chitosan solution by weight, stir evenly, and obtain a second additive solution; S03: The first additive liquid and the second additive liquid were mixed in a weight ratio of 5:3, and ball-milled at a speed of 1500 r / min for 2 h to obtain a modified liquid; S04: adding the irradiated glass fiber to a modification liquid of 5.5 times the total weight of the irradiated glass fiber, stirring and modifying the fiber, and after the stirring is completed, filtering and drying are performed to obtain the modified glass fiber.

[0057] The mass fraction of the sodium silicate solution in this embodiment is 5%; the pH value of the phosphate buffer solution is 5.5; and the mass fraction of the chitosan solution is 4%.

[0058] The stirring speed of the stirring modification treatment in this embodiment is 600 r / min, and the stirring is 30 min.

[0059] The preparation method of the tonic stimulant of this embodiment is as follows: S11: preheating the flaky talc at 57.5° C. for 1 h, then immersing the preheated flaky talc in a lanthanum chloride solution with a weight that is 4 times the total weight of the preheated flaky talc, stirring at a stirring speed of 600 r / min for 2 h, and after the stirring is completed, filtering and drying to obtain a flaky talc agent doped with lanthanum; S12: The lanthanum-doped flaky talc and the strength-regulating and tonic liquid are mixed in a weight ratio of 5:3, and the mixture is ball-milled at a speed of 1250 r / min for 1 h. After the ball-milling is completed, the mixture is filtered and dried to obtain the strength-regulating and tonic agent.

[0060] The mass fraction of the lanthanum chloride solution of the present embodiment is 4.5%.

[0061] The strength-regulating and tonic liquid of this embodiment comprises the following raw materials in parts by weight: 3.5 parts of nano-alumina, 5 parts of sodium lignin sulfonate solution, 2.5 parts of hydroxyapatite, 1.5 parts of yttrium oxide and 1.5 parts of sodium alginate solution.

[0062] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 6.5%; the mass fraction of the sodium alginate solution is 4.5%.

[0063] The preparation process of a flame retardant fiber fireproof heat-insulating knitted composite cotton of this embodiment includes the following steps: Step 1, preparing a knitted cotton base layer 1; Step 2: preparing the fiber layer 2, and arranging the fiber layer 2 on the upper surface and the lower surface of the knitted cotton base layer 1; Step 3, prepare the resin composite: the modified glass fiber, glass beads, magnesium hydroxide flame retardant, tonic agent and resin are mixed evenly to obtain the resin composite; the resin layer 3 is formed by molding and curing the resin composite on the outer surface of the fiber layer 2 away from the knitted cotton base layer 1, and the flame retardant fiber fireproof and heat-insulating knitted composite cotton is obtained.

[0064] Comparative Example 1: The difference from Example 3 is that no modified glass fiber is added.

[0065] Comparative Example 2: The difference from Example 3 is that S01 treatment is not used in the preparation of the modified glass fiber.

[0066] Comparative Example 3: The difference from Example 3 is that no modifying liquid treatment is used in the preparation of the modified glass fiber.

[0067] Comparative Example 4: The difference from Example 3 is that no tonic enhancer is added.

[0068] Comparative Example 5: The difference from Example 3 is that step S01 is not used in the preparation of the tonic enhancer.

[0069] Comparative Example 6: The difference from Example 3 is that no strengthening and replenishing liquid treatment is used in the preparation of the strengthening and replenishing agent.

[0070] Comparative Example 7: The difference from Example 3 is that no nano-alumina and hydroxyapatite are added to the strength-modulating and tonic liquid.

[0071] Comparative Example 8: The difference from Example 3 is that no yttrium oxide and sodium alginate solution are added to the strength-modulating and tonic solution.

[0072] The products of Examples 1 to 3 and Comparative Examples 1 to 8 were subjected to thermal insulation and flame retardancy tests under normal conditions. At the same time, the products were immersed in water for 12 hours, and then placed under 2% hydrochloric acid mist conditions for 12 hours, and then placed under 5% hydrochloric acid mist conditions for 12 hours, and then tested for thermal insulation and flame retardancy under corrosion resistance and immersion conditions. The test results are shown in Table 1.

[0073] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 8: It can be seen from Comparative Examples 1-8 and Examples 1-3 that the product of Example 3 has excellent thermal conductivity and limiting oxygen index, and the thermal insulation and flame retardancy of the product can be improved in a coordinated manner. At the same time, the product has significant corrosion resistance and performance stability under water immersion conditions; When neither modified glass fiber nor any of the conditioning and strengthening agents are added to the product, the performance of the product shows a significant trend of deterioration. When the two are used in combination, the product performance is most significant. When S01 treatment and modifying liquid treatment are not used in the preparation of modified glass fiber, the performance of the product tends to deteriorate, especially when the modifying liquid treatment is not used, the performance of the product deteriorates significantly; The preparation of the tonic strengthening agent does not use the S01 step, the preparation of the tonic strengthening agent does not use the tonic strengthening liquid, the tonic strengthening liquid does not add nano-alumina and hydroxyapatite, and the tonic strengthening liquid does not add yttrium oxide and sodium alginate solution. The performance of the products has a tendency to deteriorate to varying degrees. Only the tonic strengthening agent obtained by the specific method of the present invention has the most significant product performance effect. Other methods are not as obvious as the present invention.

[0074] At the same time, the inventors of the present invention also found that the preparation of the modified liquid has a great influence on the product performance. Based on this, the present invention further explores the influence of the preparation of the modified liquid on the product performance.

[0075] Experimental Example 1: The only difference from Example 3 is that the first additive liquid is not added in the preparation of the modified liquid.

[0076] Experimental Example 2: The only difference from Example 3 is that no kaolin powder or sodium silicate solution is added to the first additive solution.

[0077] Experimental Example 3: The only difference from Example 3 is that boron nitride is not added to the first additive solution, and the phosphate buffer solution is replaced by water.

[0078] Experimental Example 4: The only difference from Example 3 is that the second additive liquid is not added in the preparation of the modified liquid.

[0079] Experimental Example 5: The only difference from Example 3 is that no silicon carbide whiskers are added to the second additive liquid.

[0080] Experimental Example 6: The only difference from Example 3 is that sodium carboxymethyl cellulose is not added to the second additive solution, and the chitosan solution is replaced by water.

[0081] The products of Experimental Examples 1 to 6 were subjected to thermal insulation and flame retardancy tests under normal conditions. At the same time, the products were immersed in water for 12 hours, and then placed under 2% hydrochloric acid mist conditions for 12 hours, and then placed under 5% hydrochloric acid mist conditions for 12 hours, and then tested for thermal insulation and flame retardancy under corrosion resistance and immersion conditions. The test results are shown in Table 2.

[0082] Table 2 Product performance test results of Experimental Examples 1 to 6: It can be seen from Experimental Examples 1-6 that the performance of the product changes when the first additive liquid and the second additive liquid are not added in the preparation of the modified liquid. Among the factors of the modified liquid preparation, the performance deterioration is the most obvious, followed by the fact that kaolin powder and sodium silicate solution are not added to the first additive liquid, boron nitride is not added to the first additive liquid, the phosphate buffer solution is replaced by water, and silicon carbide whiskers, sodium carboxymethyl cellulose, and chitosan solution are not added to the second additive liquid. The performance of the product has a tendency to deteriorate. Only the modified liquid obtained by the combination of the first additive liquid and the second additive liquid obtained by the specific method of the present invention has the most significant performance effect of the product, and the use of other methods instead is not as significant as the effect of the present invention.

[0083] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0084] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A flame retardant fiber fireproof heat insulation knitted composite cotton, characterized in that: The invention comprises a knitted cotton base layer (1), wherein a fiber layer (2) is fixedly provided on the upper surface and the lower surface of the knitted cotton base layer (1), and the two fiber layers (2) are woven by polyester fiber and spandex fiber in a weight ratio of 1:1; and a resin layer (3) is fixedly provided on the outer surfaces of the two fiber layers (2) away from the knitted cotton base layer (1), and the resin layer (3) is formed by molding and curing a resin composite, wherein the molding and curing temperature is 130-135°C, the molding pressure is 10Mpa, and the molding time is 12 hours.

2. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 1, characterized in that: The resin composite comprises the following raw materials in parts by weight: 10-15 parts of modified glass fiber, 5-8 parts of glass microspheres, 4-7 parts of magnesium hydroxide flame retardant, 6-10 parts of strengthening agent, 45-55 parts of resin; The resin body is prepared by using bisphenol A epoxy resin, dicyandiamide curing agent, 1-benzyl-2-methylimidazole, and silane coupling agent KH560 in a weight ratio of 50:10:3:2; The preparation method of the modified glass fiber is: S01: placing the glass fiber in a sufficient amount of a hydrogen peroxide solution with a mass fraction of 5-8%, stirring and mixing well, then washing and drying to obtain dry glass fiber; placing the dry glass fiber in a proton irradiation box for irradiation for 20-30 minutes, with an irradiation power of 350-400W, and completing the irradiation to obtain irradiated glass fiber; S02: adding 4-6 parts of kaolin powder and 1-3 parts of sodium silicate solution to 5-8 parts of phosphate buffer solution by weight, and then adding 2-4 parts of boron nitride, stirring evenly, to obtain a first addition solution; Add 3-5 parts of silicon carbide whiskers and 2-4 parts of sodium carboxymethyl cellulose to 5-8 parts of chitosan solution by weight, and stir evenly to obtain a second additive solution; S03: The first additive liquid and the second additive liquid were mixed in a weight ratio of 5:3, and ball-milled at a speed of 1500 r / min for 2 h to obtain a modified liquid; S04: adding the irradiated glass fiber to a modification liquid of 4-7 times the total weight of the irradiated glass fiber, stirring and modifying the fiber, and after the stirring is completed, filtering and drying to obtain the modified glass fiber.

3. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 2, characterized in that: The mass fraction of the sodium silicate solution is 4-6%; the pH value of the phosphate buffer solution is 5.5; and the mass fraction of the chitosan solution is 3-5%.

4. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 2, characterized in that: The stirring speed of the stirring modification treatment is 550-650r / min, and the stirring is for 30 minutes.

5. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 2, characterized in that: The preparation method of the tonic agent is as follows: S11: preheating the flaky talc at 55-60° C. for 1 h, then immersing the preheated flaky talc in a lanthanum chloride solution 3-5 times the total weight of the preheated flaky talc, stirring at a stirring speed of 500-700 r / min, stirring for 2 h, and after the stirring is completed, filtering and drying to obtain a flaky talc agent doped with lanthanum; S12: The lanthanum-doped flaky talc and the strength-regulating and tonic liquid are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain the strength-regulating and tonic agent.

6. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 5, characterized in that: The mass fraction of the lanthanum chloride solution is 3-6%.

7. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 5, characterized in that: The strength-regulating and tonic liquid comprises the following raw materials in parts by weight: 3-4 parts of nano-alumina, 4-6 parts of sodium lignin sulfonate solution, 2-3 parts of hydroxyapatite, 1-2 parts of yttrium oxide and 1-2 parts of sodium alginate solution.

8. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 7, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 5-8%; the mass fraction of the sodium alginate solution is 3-6%.

9. The flame retardant fiber fireproof heat preservation knitted composite cotton according to claim 1, characterized in that: The preparation method of the knitted cotton substrate layer is: 35-40 parts by weight of 100S / 2 cotton yarn and 30-35 parts by weight of 30D spandex yarn are knitted into cotton fabric, and then the cotton fabric is immersed in a sufficient amount of 5% by weight sodium hydroxide solution for alkali washing. After the treatment, the fabric is washed with water and dried to obtain a knitted cotton base layer.

10. A process for preparing a flame retardant fiber fireproof heat-insulating knitted composite cotton, used for preparing a flame retardant fiber fireproof heat-insulating knitted composite cotton as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: preparing a knitted cotton base layer (1); Step 2: preparing a fiber layer (2), and arranging the fiber layer (2) on the upper surface and the lower surface of the knitted cotton base layer (1); Step three: prepare a resin composite, and arrange a resin layer (3) on the outer surface of the fiber layer (2) away from the knitted cotton base layer (1), so as to obtain a flame retardant fiber fireproof heat-insulating knitted composite cotton.

Citation Information

Patent Citations

  • Environment-friendly high-resilience flame-retardant composite shell fabric

    CN108656693A

  • Flame-retardant sofa cover fabric and production method thereof

    CN108677543A

  • Preparation method of flame-retardant coated cloth

    CN109281181A

  • Environment-friendly flame-retardant low-density epoxy sheet molding compound as well as preparation method and application thereof

    CN112029235A

  • Flame-retardant insulating material plate and production method thereof

    CN112874045A

Cited By

  • High-breathability soft cotton fabric and preparation method thereof

    CN120273094A

  • Production process of functional fiber woven non-woven fabric body

    CN120867114A

  • A production process for functional fiber woven nonwoven fabric body

    CN120867114B